A novel [89Zr]-anti-PD-1-PET-CT to assess response to PD-1/PD-L1 blockade in lung cancer - Puyalto, Ander; Rodríguez-Remírez, María; López, Inés; Iribarren, Fabiola; Simón, Jon Ander; Ecay, Marga; Collantes, María; Vilalta-Lacarra, Anna; Francisco-Cruz, Alejandro; Solórzano, Jose Luis; Sandiego, Sergio; Peñuelas, Iván; et al. (Frontiers in Immunology, 2023)
Background: Harnessing the anti-tumor immune system response by targeting the program cell death protein (PD-1) and program cell death ligand protein (PD-L1) axis has been a major breakthrough in non-small cell lung cancer (NSCLC) therapy. Nonetheless, conventional imaging tools cannot accurately assess response in immunotherapy-treated patients. Using a lung cancer syngeneic mouse model responder to immunotherapy, we aimed to demonstrate that [ 89 Zr]-anti-PD-1 immuno-PET is a safe and feasible imaging modality to assess the response to PD-1/PD-L1 blockade in NSCLC.Material and methods: A syngeneic mouse model responder to anti-PD-1 therapy was used. Tumor growth and response to PD-1 blockade were monitored by conventional 2-deoxy-2-[ 18 F]fluoro-Dglucose ([ 18 F]-FDG) PET scans. Additionally, tumor lymphocyte infiltration was analyzed by the use of an [ 89 Zr]-labeled anti-PD-1 antibody and measured as 89 Zr tumor uptake. This is a provisional file, not the final typeset article Results: Conventional [ 18 F]-FDG-PET scans failed to detect the antitumor activity exerted by anti-PD-1 therapy. However, [ 89 Zr]-anti-PD-1 uptake was substantially higher in mice that responded to PD-1 blockade. The analysis of tumor-infiltrating immune cell populations and interleukins demonstrated an increased anti-tumor effect elicited by activation of effector immune cells in PD-1-responder mice. Interestingly, a positive correlation between [ 89 Zr]-anti-PD-1 uptake and the proportion of tumorinfiltrating lymphocytes (TILs) was found (Cor = 0.8; p = 0.001).Conclusions: Our data may support the clinical implementation of immuno-PET as a promising novel imaging tool to predict and assess the response of PD-1/PD-L1 inhibitors in patients with NSCLC.